THE USE OF TRANSLATION IN TEACHING WRITING NARRATIVE TEXT - Esterina Sipahutar; Masitowarni Siregar; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
THE USE OF TRANSLATION IN TEACHING WRITING NARRATIVE TEXT *Esterina Sipahutar **Masitowarni Siregar **Anni Holila Pulungan Universitas Negeri Medan ABSTRACT Sipahutar, Esterina. Registration Number: 214332101. The Use of Translation in Teaching Writing Narrative Text. A Thesis. English Educational Program, State University of Medan, 2020. This study aimed at describing the use of translation and investigating the reasons of using translation in teaching writing narrative text grade ten at SMK Broadcasting Bina Creative Medan. This study was qualitatively conducted that taken 2 English teachers of SMK Broadcasting Bina Creative Medan. The data were collected by using an interview and observing the whole process of the online teaching writing narrative text. The findings of this study showed that there were 73 times of using translation found during three processes that they were conveying and checking meaning of words or sentences, explaining grammar and classroom management. The reasons of using translation in teaching writing narrative text were facilitating communication, teacher-student relationship and the L2 learning. The findings of this study revealed that translation contributed to the study of foreign language teaching especially teaching writing skill. Keywords: translation, teaching and narrative text.